Mirror Life and the Case for Adaptive Risk Governance - David R. Gillum (Health Security, 2026)
The current conversation regarding the potential for a mirror organism, opposite in chirality to typical life on Earth, presents a unique opportunity for the biosafety and biosecurity policy communities. It allows for meaningful and productive conversation before the technology can create a complete mirror organism. Because of their unusual structure and chemistry, mirror organisms might evade immune systems or survive undetected in the environment, posing atypical concerns that current risk assessment and mitigation systems are not built to manage. Due to a lack of data about how mirror life might interact with living things, this emergent biotechnology presents a case study in how to develop a future policy framework to mitigate novel risks: flexible and adaptable, forward-looking, and ready to act before problems arise. Building on existing proposals for cautious, conditional oversight for mirror life, this commentary advances a proposal for adaptive governance, tiered checkpoints, early warning signals, institutional roles, and international coordination systems that evolve as the science develops. It also argues that with structured risk forecasting, regimented oversight, and shared global norms, it is possible to support responsible scientific innovation while protecting against the risks of mirror life.